2011
DOI: 10.1186/1742-2094-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neuroinflammation and pain hypersensitivity after peripheral nerve injury in rats expressing mutated superoxide dismutase 1

Abstract: BackgroundNeuroinflammation and nitroxidative stress are implicated in the pathophysiology of neuropathic pain. In view of both processes, microglial and astroglial activation in the spinal dorsal horn play a predominant role. The present study investigated the severity of neuropathic pain and the degree of glial activation in an inflammatory- and nitroxidative-prone animal model.MethodsTransgenic rats expressing mutated superoxide dismutase 1 (hSOD1G93A) are classically used as a model for amyotrophic lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 64 publications
2
33
0
1
Order By: Relevance
“…10S,T ). Microglia aggregates with similar characteristics have been previously observed in the injured or diseased spinal cord and shown to contain microglia with morphological and immunological hallmarks of activation (Sanagi et al, 2010;Berger et al, 2011;David and Kroner, 2011). Interestingly, Runx1 expression was detected in only a subpopulation of microglia in these aggregates, possibly because not all cells in these clusters were equally activated.…”
Section: Cip1supporting
confidence: 50%
“…10S,T ). Microglia aggregates with similar characteristics have been previously observed in the injured or diseased spinal cord and shown to contain microglia with morphological and immunological hallmarks of activation (Sanagi et al, 2010;Berger et al, 2011;David and Kroner, 2011). Interestingly, Runx1 expression was detected in only a subpopulation of microglia in these aggregates, possibly because not all cells in these clusters were equally activated.…”
Section: Cip1supporting
confidence: 50%
“…Regarding microglia, LPS triggered the gene up-regulation of CD11b in both genotypes. These changes were, however, clearly enhanced in hSOD1 G93A microglia, validating the inflammatory-prone properties of the ALS model, as suggested in vitro (Xiao et al, 2007) and in vivo (Berger et al, 2011). Down-regulation of mGluR5 was already evidenced in differentiated astrocytes treated with IL-1␤ (Aronica et al, 2005) or thrombin (Miller et al, 1996), and in naive astrocytes incubated with conditioned media from LPS-activated microglia (Tilleux et al, 2007), both at the mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 64%
“…In mouse models, NOX2 expression in the lumbar spinal cord can also be used as a marker of neuroinflammation and microgliosis (15,20). Indeed, when comparing microglia purified from SOD1 G93A mice at different stages of disease, Liao et al (108) observed that microglia at an early stage presented a neuroprotective activity while it became neurotoxic for primary motoneurons at an end stage.…”
Section: Studies In Humansmentioning
confidence: 99%